Nilai-nilai Moral Sebagai Pembangun Karakter dalam Serat Mahayana - Andreansyah Barmabi; Widyastuti, Murni (Jurnal Intelek Insan Cendikia, 2024)
The manuscript is a written work created manually before the invention of the typewriter and consists of sheets of paper. Usually, manuscripts contain the ways of living and thought patterns of a society in their daily lives. In the field of philology, a manuscript is a handwritten result that contains various expressions of human creativity, taste, and intention, usually referred to as literary works. One of the manuscripts that is the subject of this research is Serat, which in this context is a letter containing messages addressed by a person or certain parties. Serat Mahayana, written on March 15, 1941, contains the teachings of Buddha Gautama to his disciples regarding moral values. The manuscript consists of 57 statements of Buddha Gautama's teachings as a character builder for human life. This research uses qualitative research methods and a philological approach. The problem addressed in this research is the moral values contained in Serat Mahayana. The results of this research show that there are moral values contained in Serat Mahayana.